A Latent Profile Analysis of Instructor Presence in Online Teaching and Learning in Higher Education: A Students’ Evaluation Perspective - Appianing, Joseph; Quansah, Frank; Ansah, Seth; Amoako, Roger; Frimpong, Godwin (Universitas Negeri Padang, 2025)
This study examined instructor presence in the context of online learning in Ghanaian higher education by focusing on the post-COVID-19 virtual teaching environment. Grounded in the Community of Inquiry framework, the study specifically examined how instructors create teaching, cognitive, social, and emotional presences that foster students’ engagement in the online learning environment. We collected data from 404 postgraduate students using a self-administered online questionnaire comprising 39 items. We used Latent Profile Analysis to classify instructors into four groups: novice, intermediate, promising, and ideal, based on their ability to create these presences. The results indicate that the dominant presence is teaching, but barriers such as low technological readiness and digital literacy make the cognitive and social presences less evident. The results also indicate that emotional presence, which strongly correlates with other presences, is the second most important presence the instructors created. The students' perceptions of the instructor's presence did not vary based on their gender, suggesting that the instructors' proficiency in online teaching is comparable, potentially enhancing the uniformity of the learning experience across various student groups. This paper underscores the need for faculty development that addresses training on technology-enhanced pedagogy and emotional intelligence for online teaching. Specific recommendations relate to targeted support for instructors teaching online courses, the development of technological resources, and support for enhancing cognitive and social presences in virtual classrooms.